2020
DOI: 10.3390/app10217664
|View full text |Cite
|
Sign up to set email alerts
|

On the Adoption of Global/Local Approaches for the Thermomechanical Analysis and Design of Liquid Rocket Engines

Abstract: Large Liquid Rocket Engines for Aerospace applications usually need to be cooled regeneratively since they are characterized by high pressure levels and heat flux with the presence, in the inner structure, of very high thermal gradients—thus necessitating the adoption of elastic-plastic nonlinear material models to study the thermomechanical behavior of the chamber and its service life. Tackling such nonlinearity makes the finite element analyses computationally intensive, particularly so when dealing with thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The transient thermal behaviour of cooling channels was investigated by non linear FEM analyses, considering the dependence of material properties with temperature. More information about these aspects can be found in [ 6 , 32 ].…”
Section: Structural Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The transient thermal behaviour of cooling channels was investigated by non linear FEM analyses, considering the dependence of material properties with temperature. More information about these aspects can be found in [ 6 , 32 ].…”
Section: Structural Modelmentioning
confidence: 99%
“…The parameters of multilinear isotropic model resulted by extrapolating data from experimental outcomes in terms of stabilized stress-plastic strain curves at different temperatures, available for CuCrZr material [ 19 ]. The Chaboche kinematic hardening law with three back stresses, according to the Armstrong–Frederick nonlinear model, was employed to include the kinematic hardening effects (see Figure 3 ) [ 32 , 33 , 34 ]. The combined time hardening model can be described through the following relationship: …”
Section: Structural Modelmentioning
confidence: 99%
“…The turbine pump feed system uses the pump to pressurize the propellant, which greatly reduces the mass of the tank and improves the thrust chamber pressure. These engines have high specific impulse [7][8][9]. However, the structure of these engines is complex, generally including components such as gas generators, turbines, and centrifugal pumps.…”
Section: Introductionmentioning
confidence: 99%
“…in plastic strain and stress) on the macromodel time iteration step are ignored (not being interpolated back on the macro-model at the subsequent iteration step), the prediction of the accumulated plasticity-related phenomena is less conservative. To overcome the one-way method drawbacks, some papers [18]- [21] propose to add a macromodel correction step in order to obtain a full iterative procedure. It was shown that the two-way method efficiently solves the generic structural mechanic problem [18], large assemblies [19], fuels [20], and nuclear reactors in [21].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the one-way method drawbacks, some papers [18]- [21] propose to add a macromodel correction step in order to obtain a full iterative procedure. It was shown that the two-way method efficiently solves the generic structural mechanic problem [18], large assemblies [19], fuels [20], and nuclear reactors in [21]. However, insufficient or no interest whatsoever has so far been given to the implementation of the two-way method in multiscale modeling of power IC, for assessing the thermomechanical local plasticity.…”
Section: Introductionmentioning
confidence: 99%